Cardiac Metabolism in a Pig Model of Ischemia–Reperfusion by Cardiac Magnetic Resonance with Hyperpolarized 13C-Pyruvate. (March 2015) - Aquaro, Giovanni Donato; Frijia, Francesca; Positano, Vincenzo; Menichetti, Luca; Santarelli, Maria Filomena; Lionetti, Vincenzo; Giovannetti, Giulio; Recchia, Fabio Anastasio; Landini, Luigi
Abstract: Background: Magnetic resonance (MRI) with hyperpolarized 13 C-pyruvate is a new technique for the assessment of myocardial metabolism. Aims: The aim of this study is to assess the effectiveness of MRI with hyperpolarized 13 C-pyruvate to detect cardiac metabolic changes in a model of ischemia/reperfusion. Methods: A pneumatic occluder was placed around the left anterior descending artery in 7 pigs. A 3 T scanner with a 13 C quadrature birdcage coil was used. Hyperpolarized 13 C-pyruvate was injected intravenously at rest, during coronary occlusion and 5 min after reperfusion. Metabolic images were acquired using a 3D-IDEAL spiral CSI during the injection of 13 C-pyruvate and 3D-parametric maps of 13 C-pyruvate, 13 C-lactate and 13 C-bicarbonate were generated. Metabolic Activity Mismatch (MAM) was defined as the relative change between a) resting state and coronary occlusion or b) resting and reperfusion in all the myocardial segments. Results: During occlusion, a decrease in 13 C-lactate (− 21 ± 26% vs baseline 3 ± 16%, P < 0.0001) and 13 C-bicarbonate (− 29 ± 34% vs 33 ± 52%, P < 0.0001) was found in myocardial segments at risk, as compared with remote segments. In ischemic segments, the 13 C-lactate signal increased during reperfusion (20 ± 42% vs − 7 ± 22%, P = 0.0007), while 13 C-bicarbonate was persistently reduced (− 38 ± 27% vs 36 ± 51%, p < 0.0001). Conclusions: 13 C-pyruvate MRI is able to detect transient changes in regional metabolism in an in-vivo model of myocardial ischemia–reperfusion.